2022
DOI: 10.7160/eriesj.2022.150302
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Financial Literacy in Primary School Students

Abstract: The innovative methodology of the financial literacy formation in primary school students has been theoretically substantiated, the research has been carried out on the basis of education for success in life (integration of media education, financial education and education for sustainable development) and the relationship between the pedagogy of success and the pedagogy of heart. The structure of financial literacy has been determined. The model of the methodology of formation of financial literacy in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…The data on financial literacy in the context of the linkage between the causes of family and youth financial literacy received within the present research has confirmed the conclusions obtained by other scientists (Vosylis et al, 2021;Jančius et al, 2022). Researches highlight the school's impact on youth financial literacy level (Kuzma et al, 2022;Compen et al, 2022). Only 34% of school learners of form 12 in Latgale obtained financial literacy knowledge at school.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The data on financial literacy in the context of the linkage between the causes of family and youth financial literacy received within the present research has confirmed the conclusions obtained by other scientists (Vosylis et al, 2021;Jančius et al, 2022). Researches highlight the school's impact on youth financial literacy level (Kuzma et al, 2022;Compen et al, 2022). Only 34% of school learners of form 12 in Latgale obtained financial literacy knowledge at school.…”
Section: Discussionsupporting
confidence: 89%
“…According to financial socialisation, the significant agents of financial socialisation are family (Davis et al, 2018;Wann and Burke-Smalley, 2021) and school (Kuzma et al, 2022) positively affect the financial literacy of adults. Financial literacy and school-related variables also have a direct effect on economic behaviour.…”
Section: Theoretical Aspects Of Youth Financial Literacymentioning
confidence: 99%
See 2 more Smart Citations
“…También, Mena-Campoverde (2022) la define como un constructo multidimensional que puede medirse por medio de comportamientos, actitudes y conocimientos financieros. Por otra parte, Kuzma et al (2022) precisan que la alfabetización financiera es un conjunto de habilidades y conocimientos que ayudan a tomar adecuadas decisiones en el aspecto económico y financiero de la vida cotidiana. Tomando la base de datos de inclusión financiera del Banco Mundial en 2014, Demirgüç-Kunt et al (2016) han afirmado que para el año 2014, el 62% de las personas adultas en el mundo tenía una cuenta en alguna institución financiera, y que en las economías en desarrollo había un drástico crecimiento de nuevos usuarios de cuentas, así como un incremento sustancial en las transacciones financieras en forma virtual.…”
Section: Deunclassified